PANCASILA AS THE ETHIC OF PEACE IN INDONESIA’S INDEPENDENT AND ACTIVE FOREIGN POLICY - Nuraeni, Nuraeni; Santoso, Heri; Utomo, Agus Himawan (Sosiohumaniora, 2025)
This article aims to analyze Pancasila within the framework of philosophical discourse, emphasizing its ethical dimensions and its role in promoting peace. The doctrine of the Independent and Active Foreign Policy serves as Indonesia’s principal vision, striving to embody the principles, ideals, and aspirations for a more peaceful, just, and civilized global society. Employing a qualitative research methodology anchored in philosophical inquiry, this study systematically and reflectively examines Pancasila as the ethical foundation for peace, exploring its pertinence to the evolution and dynamics of Indonesian foreign policy from 1945 to 2024. The findings indicate that Pancasila functions as both the ideological foundation and a moral framework for Indonesia’s foreign policy, particularly in promoting peace. Implementing this policy requires a deep understanding of peace as an aspirational goal, moving beyond rhetoric to further societal change. The principles embodied in Pancasila encompass ethical standards that serve as a guiding framework for Indonesia’s diplomatic stance and international engagement. As the ethic of peace, Pancasila renders Indonesia’s foreign policy adaptable to varying international dynamics while emphasizing the importance of domestic diversity experiences as a vital asset in managing the intricacies of international relations.